Evapotranspiration and water availability response to climate change in the Middle East and North Africa - Salah Basem Ajjur (14150967) (2021)
Quantifying the impact of climate change on evapotranspiration is necessary for devising accurate water and energy budgets in light of global warming. Nevertheless, in the Middle East and North Africa (MENA), little has been done to bridge this gap. This study, then, implements Penman and Budyko approaches to climatic data retrieved from the sixth phase of the Coupled Model Intercomparison Project (CMIP6) to assess evapotranspiration and water availability evolutions through the twenty-first century. Outcomes reveal that the MENA region is indeed vulnerable to a surge in temperature, which can increase evapotranspiration losses and decrease water availability. Under the shared socioeconomic pathway (SSP2-4.5), the potential evapotranspiration (PET) has been projected to increase throughout the MENA region by up to 0.37 mm per year during the middle of the twenty-first century (2021–2050) and by up to 0.51 mm per year during the end of the twenty-first century (2071–2100). Meanwhile, the actual evapotranspiration (AET) has been projected to increase by up to 0.3 (~0.2) mm per year before 2050 (2100). The trends in both projections (PET and AET) are exaggerated under SSP5-8.5. The analysis predicted a shortage of water availability (precipitation—AET), which is alarming for most MENA regions. Relative to the reference period (1981–2010), the decline in annual water availability would reach 26 (62) mm by 2100 under SSP2-4.5 (SSP5-8.5). The rise in temperatures appears to be the principal reason for MENA and water availability responses. This study’s outcomes can facilitate accurate and realistic predictions related to evapotranspiration and water availability, which are key elements in not only managing water resources but also in devising effective climate change mitigation and adaptation plans. Other Information Published in: Climatic Change License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10584-021-03122-z